Effect of tablets containing lactoferrin and lactoperoxidase on gingival health in adults: A randomized, double‐blind, placebo‐controlled clinical trial. (10th July 2019) - Nakano, Manabu; Yoshida, Akihiro; Wakabayashi, Hiroyuki; Tanaka, Miyuki; Yamauchi, Koji; Abe, Fumiaki; Masuda, Yuji
Abstract: Objective: To evaluate the effect of tablets containing lactoferrin (LF) and lactoperoxidase (LPO) on gingival health and oral health‐related quality of life in healthy adults. Background: Lactoferrin and LPO are host defense factors found in saliva that may contribute to oral health. Materials and Methods: One hundred and fifty adults were randomly assigned to the administration of high‐dose tablets (LF 60 mg/d, LPO 7.8 mg/d), low‐dose tablets (LF 20 mg/d, LPO 2.6 mg/d), or placebo tablets for 12 weeks. The gingival index (GI) and plaque index (PlI) were measured at baseline and after 12 weeks. Oral health‐related quality of life was assessed by the Oral Health Impact Profile (OHIP) at baseline and at 4, 8, and 12 weeks. Results: One hundred and nine healthy subjects were included in the efficacy analysis. In the high‐dose group, the GI was significantly reduced after 12 weeks of treatment, and the reduction in GI in the high‐dose group was significant compared with the placebo group. In both the high‐dose group and the low‐dose group, PlI showed a significant decrease at 12 weeks compared with baseline. The total OHIP score was significantly reduced at 12 weeks in the high‐dose group. In addition, the OHIP functional limitation subscale displayed significant improvement in the high‐dose groups compared with the placebo group at 12 weeks. No adverse reactions or serious adverse events related to the test tablets were observed in any of participants during the study, and the incidence of adverse events unrelated to the tablets did not differ significantly among the groups. Conclusion: These results suggest that intake of tablets containing LF (60 mg/d) and LPO (7.8 mg/d) can potentially improve gingival inflammation and oral health‐related quality of life in healthy adults.